2017
DOI: 10.1063/1.4975179
|View full text |Cite
|
Sign up to set email alerts
|

Design, construction, and performance of a device for directional recrystallization of metallic alloys

Abstract: A device was designed to apply the directional recrystallization method to Fe-based alloys in order to obtain bamboo-like microstructures. This microstructure is suitable for improving creep properties and resistance to fatigue in some alloys and for enhancing pseudoelastic properties in shape memory alloys. The design and construction of a flat coil are described in detail. In addition, we developed an electromechanical system to control the movement of a wire within the flat coil. The construction details an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The heating source, cooling method and temperature gradient noted in various papers are listed in Table 2. For furnaces where the heating unit moves when the sample is static [6,18,[20][21][22][23]25,28,30,31,33,35,50], the temperature gradient often changes continuously during processing since the distance between the heating unit and heat sink changes; while for furnaces where the sample travels when the heating unit is static [8,[35][36][37][38][39][40][41][43][44][45][46]48,49,[52][53][54][55][56][57][58], the temperature gradient is usually constant as long as the sample is long enough. It is clear that static heating unit design is better for directional recrystallisation research since the temperature gradient is well controlled.…”
Section: Temperature Gradientmentioning
confidence: 99%
See 2 more Smart Citations
“…The heating source, cooling method and temperature gradient noted in various papers are listed in Table 2. For furnaces where the heating unit moves when the sample is static [6,18,[20][21][22][23]25,28,30,31,33,35,50], the temperature gradient often changes continuously during processing since the distance between the heating unit and heat sink changes; while for furnaces where the sample travels when the heating unit is static [8,[35][36][37][38][39][40][41][43][44][45][46]48,49,[52][53][54][55][56][57][58], the temperature gradient is usually constant as long as the sample is long enough. It is clear that static heating unit design is better for directional recrystallisation research since the temperature gradient is well controlled.…”
Section: Temperature Gradientmentioning
confidence: 99%
“…A transverse temperature gradient can be present in some directional annealing studies, especially with large samples and using induction heating, in which a transverse temperature gradient is induced by the skin effect. Using the finite element method, Liu et al [54] showed that for a five-turn induction coil furnace (cross-section of 60 × 60 mm 2 ), a transverse temperature gradient was observed when the iron sample diameter was larger than 20 mm and that it increased with increasing sample Air-impingement cooling 844 [15] Induction coil Ambient air cooling 25 [35] Focused light radiation Ambient air cooling 50 [35][36][37]43,53,53,55,56] Focused light radiation Water-cooled copper 1000 [38][39][40][41][42]44,48] Induction coil Liquid Ga-In cooling bath 200-350 [45,47] Resistance heating Ambient air cooling 82 [46] Induction coil Water cooling bath 900 [49] Induction coil Water-cooled chill block 200 [55] Induction coil Water cooling bath 680 [57] Induction coil Ambient air cooling 180 diameter. Thus, a transverse temperature gradient can undoubtedly affect the directional recrystallised structure in different parts of the material.…”
Section: Temperature Gradientmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, pseudoelasticity reaches a large efficiency if single crystals are considered [15,22,23]. In this way, Vallejos et al developed a method based on thermal cycling with a simultaneous directional annealing, which leads to single crystals after a short time interval [24,25].…”
Section: Introductionmentioning
confidence: 99%